Indian Polyvalent Antivenom Accelerates Recovery From Venom-Induced Consumption Coagulopathy (VICC) in Sri Lankan Russell’s Viper (Daboia russelii) Envenoming - Silva, Anjana; Scorgie, Fiona E.; Lincz, Lisa F.; Maduwage, Kalana; Siribaddana, Sisira; Isbister, Geoffrey K. (Frontiers in Medicine, 2022)
Background Venom induced consumption coagulopathy (VICC) is an important clinical consequence of Russell’s viper (Daboia russelii) envenoming. There is limited evidence for antivenom effectiveness in resolving VICC. We aimed to compare the recovery of VICC in patients who received and did not receive antivenom following Russell’s viper envenoming. Methodology This was a non-randomised observational study comparing patients with VICC from Russell’s viper envenoming given antivenom for systemic envenoming and those not given antivenom . Antivenom administration was decided by the treating physicians. We included 44 patients with confirmed Russell’s viper bites with one or more International Normalised Ratio (INR) value ≥1.5 (VICC). We compared five patients who did not receive antivenom with 39 patients who did receive antivenom. The primary outcome was the proportion of patients with an INR <1.5 by 48h post-bite. Results The antivenom group had higher peak serum venom concentrations (median (IQR) = 272 (96-1076) ng/mL versus 21 (8-58) ng/mL) and more severe VICC compared to the no antivenom group. Twenty seven of 39 patients (69%) in the antivenom group had an INR <1.5 at 48h post-bite compared to none of the five patients (0%) in the no antivenom group (absolute difference: 69%; 95%CI: 13 to 83%; p=0.006; Fisher’s exact test). The fibrinogen recovered in 32 of 39 patients (82%) in the antivenom group compared to one of five patients (20%) in the no antivenom group (absolute difference 62%; 95% CI: 28 to 95%; p=0.001; Fisher’s exact test). Both INR and fibrinogen were significantly improved between 24 and 48h post-bite in the antivenom group compared to the no antivenom group. Conclusion Antivenom accelerated the recovery of VICC in patients with Russell’s viper envenoming, compared to no recovery in a smaller group of patients with milder VICC not receiving antivenom. This supports the efficacy of antivenom in patients with VICC.